1996
DOI: 10.1111/j.1744-7348.1996.tb05731.x
|View full text |Cite
|
Sign up to set email alerts
|

Detection of pineapple bacilliform virus using the polymerase chain reaction

Abstract: A polymerase chain reaction (PCR) assay has been developed to detect pineapple bacilliform virus (PBV) in extracts from infected plants. Initially, degenerate primers were designed from conserved badnavirus amino acid sequences and used in PCR with partially purified PBV preparations. A 448 bp DNA fragment was amplified from a region in the reverse transcriptase and ribonuclease H genes. The nucleotide sequence of the cloned PCR product indicated that PBV was related to, but distinct from, other badnaviruses. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…Several mealybug species are vectors of viral diseases of various crops: banana (Kubiriba et al 2001;Thomson et al 1996;Watson and Kubiriba 2005), black pepper (Bhat et al 2003), cocoa (Dufour 1991;Entwistle and Longworth 1963;Hall 1945), grapevine (Cabaleiro and Segura 1997a, b;Cid et al 2007;Garau et al 1995;Minafra and Hadidi 1994;Petersen and Charles 1997;Sforza et al 2003;Tsai et al 2008;Zorloni et al 2006), pineapple (Sether and Hu 2002a, b;Sether et al 1998Sether et al , 2005, rice (Abo and Sy 1998), and sugarcane (Lockhart et al 1992). …”
Section: Economic Importance Of Mealybugsmentioning
confidence: 99%
“…Several mealybug species are vectors of viral diseases of various crops: banana (Kubiriba et al 2001;Thomson et al 1996;Watson and Kubiriba 2005), black pepper (Bhat et al 2003), cocoa (Dufour 1991;Entwistle and Longworth 1963;Hall 1945), grapevine (Cabaleiro and Segura 1997a, b;Cid et al 2007;Garau et al 1995;Minafra and Hadidi 1994;Petersen and Charles 1997;Sforza et al 2003;Tsai et al 2008;Zorloni et al 2006), pineapple (Sether and Hu 2002a, b;Sether et al 1998Sether et al , 2005, rice (Abo and Sy 1998), and sugarcane (Lockhart et al 1992). …”
Section: Economic Importance Of Mealybugsmentioning
confidence: 99%
“…In this study, the PCR-based diagnostic assay used for the detection of badnavirus sequences was similar to those used successfully for detection of many badnavirus sequences in different tropical food crops such as banana (Geering et al, 2000), cacao (Muller et al, 2001), pineapple (Thomson et al, 1996), sugarcane (Braithwaite et al, 1995), taro (Yang et al, 2003) and yam (Eni et al, 2008;Kenyon et al, 2008;Lima et al, 2013). All the PCR tested samples collected from IITA were badnavirus positive.…”
Section: Pcr Detection Of Yam Badnavirus Sequencesmentioning
confidence: 99%
“…Wakman et al (1995) also observed two distinct serotypes of closterovirid from Australian pineapples, which were named Pineapple closterovirus A and B, but it is not known how these viruses relate to the viruses described from Hawaii. During this study, a bacilliform-shaped virus was also detected in pineapples in Australia (Wakman et al 1995), which from particle size and morphology, and later, sequence analysis (Thomson et al 1996), was most likely a member of the genus Badnavirus. PMWaV-1 was detected in a small number of samples of Australian pineapples but PMWaV-2, -3 and -4 have not previously been reported.…”
Section: Introductionmentioning
confidence: 99%